The Personal Selling: Upaya Optimal Marketing di Shenzen Menarik Minat Konsumen Membeli Produk Sutra - Tini, Tien Yus; Mahesa, Putra Anugrah (Jurnal Pengabdian kepada Masyarakat (ABDIKEMAS), 2025)
This Community Service (PkM) activity aims to improve the personal selling skills of silk product entrepreneurs in Shenzhen, China, in facing increasingly fierce market competition. Mentoring was provided through field observations, training, simulations, and hands-on practice with silk traders. Results showed significant improvements in interpersonal communication skills, product demonstrations, mastery of sales materials, and persuasion techniques. These improvements resulted in increased consumer interest and increased sales success rates. This activity demonstrated that personal selling is an effective strategy for increasing the appeal and sales of high-value traditional craft products such as silk.